The impact of inadequate and dysfunctional training on Agile transformation process: a grounded theory study - Gandomani, Taghi Javdani; Zulzalil, Hazura; Abd Ghani, Abdul Azim; Md Sultan, Abu Bakar; Parizi, Reza Meimandi (Elsevier, 2015)
Context Training is an essential facilitator in moving from traditional to Agile software development. Objective This paper addresses the importance of adequate and functional training in Agile transformation process, the causes of inadequate and dysfunctional training, and the heuristic strategies that can be used in software companies for dealing with this phenomenon. Method A Grounded Theory study was conducted with participation of 35 Agile experts from 13 different countries. Results This research discovered that inadequate and dysfunctional training was one of the critical issues that affected Agile transformation process. This study shows that comprehensive and functional training is not often provided to support Agile transformation. This paper shows the primary causes of inadequate and dysfunctional training, its adverse consequences on the transformation process, and the heuristic and ad-hoc treatments as the strategies used by Agile teams to cope with this challenge. Conclusion Comprehensive training is important in Agile transformation process. Inadequate and dysfunctional training causes several challenges and problems for software companies and development teams when moving to Agile. Several ad-hoc strategies identified by this study can be employed to help software teams and companies facing similar problems.